Impact of COVID-19 on Rocky Vista University medical students’ mental health: A cross-sectional survey - Paz, Dean C.; Bains, Manav Singh; Zueger, Morgan L.; Bandi, Varasiddimounish R.; Kuo, Victor Y.; Payton, Mark; Ryznar, Rebecca Jean (Frontiers in Psychology, 2023)
Background: The COVID-19 pandemic brought immense changes to medical school curriculums world-wide, such as the widespread adoption of virtual learning. We sought to better understand the impact on medical students’ mental health at Rocky Vista University College of Osteopathic Medicine, Parker, CO, USA. This study assessed the impact the pandemic had on anxiety and depression levels of medical students. It also assessed the impact of several domains on student mental health during the pandemic and how various sub-groups within the studied population were affected. Methods: A cross-sectional survey was sent to students through an online anonymous google survey in May to June 2021, centered around the 7-item questionnaire used to screen for Generalized Anxiety Disorder GAD-7, 9-item questionnaire used to screen for depression PHQ-9, and self-designed questions to assess the personal impact of the pandemic. Data obtained were screened for error and analyzed with significance value of p<0.05. Results: A total of 152 responses were received (25.5% response rate). Of these, 64.1% identified as female, 75.8% were white, 50.3% were between ages 21-25, and 77.8% were first year medical students. During the pandemic, 79.6% of respondents felt more anxious and 65.1% felt more depressed. 67.8% of students reported feeling social isolation amidst the pandemic. Students living with friends were more likely to see a therapist for depression during the pandemic (p=0.0169) and prescribed an antidepressant (p=0.0394). Females and students in relationships were more likely to score higher on GAD-7 (p=0.0194) and (p=0.0244), respectively. Conclusion: This study investigated the effect of the pandemic on medical students’ mental health and the need to address this issue. Results suggest that the pandemic had a negative impact on medical student’s mental health and that anxiety and depression levels worsened for pre-clinical medical students at Rocky Vista University. As such, it is imperative to incorporate additional resources to protect the well-being of medical students as they progress through their medical careers.